2009
DOI: 10.1128/aem.02407-08
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Fastidious Bacteria by Viability Staining and Micromanipulation in a Soil Substrate Membrane System

Abstract: Soil substrate membrane systems allow for microcultivation of fastidious soil bacteria as mixed microbial communities. We isolated established microcolonies from these membranes by using fluorescence viability staining and micromanipulation. This approach facilitated the recovery of diverse, novel isolates, including the recalcitrant bacterium Leifsonia xyli, a plant pathogen that has never been isolated outside the host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The fact that the overwhelming part of microbial diversity remains uncultivated and unexplored presents exciting opportunities for basic and applied discoveries. The renewed interest in microbial cultivation (1,5,7,8,14,15,33,42) has led to the development of several innovative approaches to bring new species into culture. Most of these approaches share one basic strategy: to mimic the environment of target organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the overwhelming part of microbial diversity remains uncultivated and unexplored presents exciting opportunities for basic and applied discoveries. The renewed interest in microbial cultivation (1,5,7,8,14,15,33,42) has led to the development of several innovative approaches to bring new species into culture. Most of these approaches share one basic strategy: to mimic the environment of target organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, Ferrari and coworkers had cultured microcolonies of rare soil bacteria by growing them on filters suspended on soil slurry in the absence of added nutrients (22). Micromanipulation was used to grow one isolate in pure culture, and a follow-up study showed that these microcolonies could be reliably micromanipulated for downstream cultivation (23).…”
Section: Approaches To Culturing the Missing Bacterial Diversitymentioning
confidence: 99%
“…Some media that are traditionally used for soil microbiological studies returned low viable counts and did not result in the isolation of members of rarely isolated groups. Like the Soil extract agar as used by [2] and [5]. Newly developed media in contrast resulted in high viable counts and in the isolation of members of rarely isolated group regardless of the inoculums size [8].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of growth media and incubation time were investigated in viable counts as described by [5], [9]and [10]. Some media that are traditionally used for soil microbiological studies returned low viable counts and did not result in the isolation of members of rarely isolated groups.…”
Section: Discussionmentioning
confidence: 99%